Effects of COVID-19 on the Human Central Olfactory System: A Natural Pre-Post Experiment - Thunell, E.; Peter, M.G.; Lenoir, V.; Andersson, P.; Landis, B.N.; Becker, M.; Lundström, J.N. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: Reduced olfactory function is the symptom with the highest prevalence in coronavirus disease 2019 (COVID-19) with nearly 70% of infected individuals experiencing partial or total loss of their sense of smell at some point during the disease. The exact cause is not known, but beyond peripheral damage, studies have demonstrated insults to both the olfactory bulb and central olfactory brain areas. However, these studies often lack both baseline pre-COVID-19 assessments and control groups, and the effects could, therefore, simply reflect pre-existing risk factors.MATERIALS AND METHODS: Shortly before the COVID-19 outbreak, we completed an olfactory-focused study, which included structural MR brain images and a full clinical olfactory test. Opportunistically, we invited participants back 1 year later, including 9 participants who had experienced mild-to-moderate COVID-19 (C19+) and 12 who had not (C19−), creating a natural pre-post experiment with a control group.RESULTS: Despite C19+ participants reporting subjective olfactory dysfunction, few showed signs of objectively altered function. Critically, all except 1 individual in the C19+ group had reduced olfactory bulb volume (average reduction, 14.3%), but this did not amount to a significant statistical difference compared with the control group (2.3%) using inference statistics. We found no morphologic differences in olfactory brain areas but stronger functional connectivity between olfactory brain areas in the C19+ group at the postmeasure.CONCLUSIONS: Our data suggest that COVID-19 might cause long-term reduction in olfactory bulb volume and altered functional connectivity but with no discernible morphologic differences in cerebral olfactory regions.C19+positive for COVID-19C19−negative for COVID-19COVID-19coronavirus disease 2019OBolfactory bulbSARS-CoV-2Severe Acute Respiratory Syndrome coronavirus 2